Fauna of Cladocera and Copepoda from Xinjiang Uyghur Autonomous Region (China) - Chertoprud, Elena S.; Sinev, Artem Y.; Dimante-Deimantovica, Inta (Zootaxa, 2017)
This study evaluates the species composition of Cladocera and Copepoda in the five lakes of the Bogda-Shan Mountain range and in the floodplain of the Tarim and Konchedarya rivers located in the Xinjiang Uygur Autonomous Region of China (Xinjiang). We collected seven species of Cladocera and six species of Copepoda. Seven species were identified as new for Xinjiang fauna, and two species (Cyclops cf. herberti Einsle, 1996, and Eucyclops roseus Ishida, 1997) were first records for China. Herein, we characterize the distribution ranges for the detected species and provide taxonomic remarks. The total species list for water bodies in Xinjiang compiled from original data and available literature includes 56 species of Cladocera and 33 species of Copepoda. We also discuss the biogeographical structure of Cladocera and Copepoda faunas in Xinjiang.